2018
DOI: 10.7554/elife.32733
|View full text |Cite
|
Sign up to set email alerts
|

The small molecule ISRIB rescues the stability and activity of Vanishing White Matter Disease eIF2B mutant complexes

Abstract: eIF2B is a dedicated guanine nucleotide exchange factor for eIF2, the GTPase that is essential to initiate mRNA translation. The integrated stress response (ISR) signaling pathway inhibits eIF2B activity, attenuates global protein synthesis and upregulates a set of stress-response proteins. Partial loss-of-function mutations in eIF2B cause a neurodegenerative disorder called Vanishing White Matter Disease (VWMD). Previously, we showed that the small molecule ISRIB is a specific activator of eIF2B (Sidrauski et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
134
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(145 citation statements)
references
References 47 publications
11
134
0
Order By: Relevance
“…We used ISRIB, an ISR inhibitor (15)(16)(17)(18), in VWM mice to modulate the deregulated ISR and study the impact of this modulation on the disease. ISRIB stabilizes the eIF2B complex by direct binding (16,19,20). As a consequence, ISRIB enhances eIF2B activity, which reduces the expression of ATF4 and impacts expression of the ATF4-regulated transcriptome (16,18,19).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used ISRIB, an ISR inhibitor (15)(16)(17)(18), in VWM mice to modulate the deregulated ISR and study the impact of this modulation on the disease. ISRIB stabilizes the eIF2B complex by direct binding (16,19,20). As a consequence, ISRIB enhances eIF2B activity, which reduces the expression of ATF4 and impacts expression of the ATF4-regulated transcriptome (16,18,19).…”
Section: Introductionmentioning
confidence: 99%
“…ISRIB stabilizes the eIF2B complex by direct binding (16,19,20). As a consequence, ISRIB enhances eIF2B activity, which reduces the expression of ATF4 and impacts expression of the ATF4-regulated transcriptome (16,18,19). The compound has been successful in treatment of a prion-infected mouse model for neurodegeneration (15).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Wong et al reported that eIF2B activation can rescue defects in GEF activity due to VWMD mutations and ameliorate disease in rodent models [22,23]. Furthermore, Wong et al reported that eIF2B activation can rescue defects in GEF activity due to VWMD mutations and ameliorate disease in rodent models [22,23].…”
Section: Vanishing White Matter Diseasementioning
confidence: 99%
“…Previous research demonstrated that VWMD mutations can lead to a decrease in GEF activity. Furthermore, Wong et al reported that eIF2B activation can rescue defects in GEF activity due to VWMD mutations and ameliorate disease in rodent models [22,23]. A particularly deleterious variant, dR483W, was dramatically restored to near full activity by ISRIB in cells.…”
Section: Vanishing White Matter Diseasementioning
confidence: 99%
“…When administered to rodents, ISRIB enhances cognition and reverses cognitive deficits due to traumatic brain injury (15) and prion-induced neurodegeneration (16). Furthermore, eIF2B activation rescues cognitive and motor function in mouse models of 65 leukoencephalopathy with vanishing white matter (VWM), a debilitating or fatal autosomal disorder associated with hundreds of mutations in all subunits of eIF2B (17,18). Remarkably, ISRIB exerts its effects without overt toxicity (12, 16) due to restoration of the cytoprotective activity of the ISR when stress levels increase (19).…”
Section: Main Textmentioning
confidence: 99%